2018
DOI: 10.1111/tri.13293
|View full text |Cite
|
Sign up to set email alerts
|

The role of Sigma-1 receptor in sex-specific heat shock response in an experimental rat model of renal ischaemia/reperfusion injury

Abstract: We previously showed that female rats are more protected against renal ischaemia/reperfusion (I/R) injury than males, which is partly attributed to their more pronounced heat shock response. We recently described that Sigma-1 receptor (S1R) activation improves postischaemic survival and renal function. 17β-estradiol activates S1R, thus here we investigated the role of sex-specific S1R activation and heat shock response in severe renal I/R injury. Proximal tubular cells were treated with 17β-estradiol, which ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…21 We and other groups have demonstrated the protective role of supplemental 17β-estradiol in animal models of renal IRI, and we have demonstrated that the presence of ERα is necessary for the improved renal IRI tolerance observed among female mice as well as the protective effect of supplemental 17β-estradiol. 1,[5][6][7][8]22,23 Additionally, estrogen has also been investigated in cardiovascular disease and cardiac IRI 7,21 ; however, large clinical studies have raised concerns that estrogen therapy may increase the risk of heart disease, venous thromboembolism, stroke, and breast cancer. 13,14 SERMs are a broad class of drugs with a variety of different tissue-specific agonist/antagonist effects on the estrogen receptor, and there is little knowledge of the effects of SERMs on renal IRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 We and other groups have demonstrated the protective role of supplemental 17β-estradiol in animal models of renal IRI, and we have demonstrated that the presence of ERα is necessary for the improved renal IRI tolerance observed among female mice as well as the protective effect of supplemental 17β-estradiol. 1,[5][6][7][8]22,23 Additionally, estrogen has also been investigated in cardiovascular disease and cardiac IRI 7,21 ; however, large clinical studies have raised concerns that estrogen therapy may increase the risk of heart disease, venous thromboembolism, stroke, and breast cancer. 13,14 SERMs are a broad class of drugs with a variety of different tissue-specific agonist/antagonist effects on the estrogen receptor, and there is little knowledge of the effects of SERMs on renal IRI.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Although the exact mechanism is not yet known, estrogen appears to exert its protective effects by ameliorating ischemia-reperfusion injury (IRI). 1,[5][6][7][8] In renal transplantation IRI results in delayed graft function (DGF), defined as requiring dialysis in the first week after transplantation. 9 DGF results in increased costs, length of stay, readmissions after transplantation, rejection, and graft failure.…”
Section: Introductionmentioning
confidence: 99%
“…Not only the outcome of AKI is better in females [22,23], but the progression of renal function deterioration during the aging process [24] as well as other chronic renal diseases [25] is also slower in females compared to males. Some studies support the protective role of female hormones (17β-estradiol, progesterone) [26][27][28]. Others highlight the negative effect of testosterone: Park et al found more severe renal injury after testosterone therapy in female, ovariectomized, and castrated male mice [29].…”
Section: Sexmentioning
confidence: 98%
“…Finally, although there are some examples of studies examining behavioral outcomes in both male and female animals, potential sex-dependent effects of S1R antagonists remain to be fully characterized. This is important, as S1R is activated by 17b-estradiol and testosterone, which bind at different sites and can exert opposing pharmacological effects [ 116 , 117 ] and sex-dependent effects of S1R antagonists on other health-related outcomes have been reported in rats [ 117 ].…”
Section: Considerations Regarding the Therapeutic Development Of S1r ...mentioning
confidence: 99%